Compost Remediation of Heavy Metals Contaminated Soils - Bolarinwa, Babatunde Oladapo (2015)
The main objective of this study is to evaluate remediation method using compost as heavy metal fixing agent for soil amendments with a view to prevent heavy metals accumulation in soil which may eventually poison the food chain. The physico-chemical parameters of different types of composts and soils used were determined. The percentage removal of heavy metals from soils treated with three different types of compost were also determined and the most effective compost for the removal of the metals was reported.